Nain, Labrador (im Winter), Missionsstation der Brüdergemeine
Black and white postcard of a group with dog sled in Nain, Labrador, around the late ninteenth century. Attached caption reads, " No.5) Nain, Labrador before 1900." Black and white postcard of a group with dog sled in Nain, Labrador, around the late ninteenth century.